Identity, Cult, and Charisma: The Contestation of Online Da'wah on @halimahalaydrus's Instagram Account - Anshori, Isa; Mukhlis, Zainal; Novita, Almi (AL-TAHRIR, 2025)
This research aims to explore and analyze how identity, cult, and charisma are formed within the context of da'wah on social media, specifically through the Instagram account @halimahalaydrus. By employing a netnographic approach, the study observes the interactions, content, and community dynamics developed on this social media platform. This method enables researchers to gain an in-depth understanding of the phenomenon of da'wah by analyzing the texts, images, and comments associated with the account. The results reveal that Ustadzah Halimah Alaydrus' identity on social media is shaped not only by her characteristics but also by the digital communication strategies she employs. Through consistent content, strong spiritual narratives, and direct engagement with her followers, Ustadzah Halimah successfully builds an image as an assertive and inspiring spiritual leader. The formation of a cult occurs not only through direct teachings but also through the active involvement of her followers on Instagram, which strengthens the bonds within the digital community. Moreover, Ustadzah Halimah's charisma is recognized and reinforced by her followers, aligning with Weber's definition, where charisma stems not only from her personal qualities but also from the acceptance of her followers. Ustadzah Halimah's charisma was not solely derived from herself, but was co-constructed by the community that formed a cult around her. Ismail Fajrie Alatas emphasizes that authority is not merely position or power, but the ability to build temporal relationships, connecting past values with the current context, and creating a community that can internalize these values (Cultivating Community). Da'wah through the Instagram account @halimahalaydrus illustrates how identity, cult, and charisma evolve in the digital age, highlighting significant changes in the construction and maintenance of religious authority.